Perancangan Standard Operating Procedure (SOP) dan Sistem Informasi Barang Masuk dan Keluar pada Ritel PT Krisna Makmur Abadi - Desi Rahmaningtias; Shinta Wahyu Hati (Politeknik Negeri Batam, 2020)
PT Krisna Makmur Abadi has yet to have a Standard Operating Procedure (SOP), especially in the process of incoming and outgoing goods, is expected to guide, assist companies in carrying out operational activities, and improve the effectiveness of employees, especially the warehouse. Source of the data obtained in the form of a document the company's history, systems and procedures for entry and exit of goods and documents related to Inventory. The method used to collect data that is used this research is to conduct interviews, observation and documentation. The method used in the data analysis is qualitative descriptive method. This research resulted in the design of the Standard Operating Procedure (SOP) as a reference standards in order to increase the effectiveness of employees of companies and applications Inventory Information System to facilitate the employees to manage Inventory in the warehouse.